Prognostic significance of α- and β2-adrenoceptor gene expression in breast cancer patients - Rivero, Ezequiel Mariano (2019)
Fil: Rivero, Ezequiel Mariano. Laboratory of Hormones and Cancer, Instituto de Biología y Medicina Experimental (IBYME) - CONICET, Ciudad Autónoma de Buenos Aires; Argentina.